Impact of epitope match on stem cell transplantation - Öğret, Yeliz; Tiryaki, Tarık Onur; Zanjani, Behnoush Nasr; Kıvanç, Demet; Kekik Çınar, Çiğdem; Yönal Hindilerden, İpek; Kalayoğlu Beşışık, Sevgi; Nalçacı, Meliha; Sargın, Deniz; Savran Oğuz, Fatma (CIG Media Group, 2023)
[Abstract Not Available]
Keywords: CT; Hematopoietic Stem Cell Transplantation; HLA-B; Epitope; Case